2016
DOI: 10.1504/ijmcs.2016.076663
|View full text |Cite
|
Sign up to set email alerts
|

The spatial distribution of foreign direct investment in R&D within host countries. An empirical examination of foreign subsidiaries in Spain

Abstract: Abstract:We discuss the patterns of foreign direct investment in R&D within host countries and provide an empirical analysis for Spain by comparing foreign subsidiaries' R&D location patterns with that of domestic plants. We find that foreign subsidiaries' R&D is strongly concentrated in Madrid and Catalonia, the two largest Spanish regional agglomerations. Networked foreign subsidiaries involved in external technology sourcing still centralise to a greater extent their R&D activities in these leading regions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…This allows language, cultural, institutional, and social barriers to be overcome, and, therefore, relationships of trust to be developed. Therefore, the global reach and strategy will determine the advantage derived from using global knowledge networks, and will benefit from a more refined division, as corporate integration strengthens the influence of the focal company within its group, and external integration directly affects innovation [22,23,30,53,56,57].…”
Section: Cooperation Network Diversity Of Companies With Fdimentioning
confidence: 99%
See 2 more Smart Citations
“…This allows language, cultural, institutional, and social barriers to be overcome, and, therefore, relationships of trust to be developed. Therefore, the global reach and strategy will determine the advantage derived from using global knowledge networks, and will benefit from a more refined division, as corporate integration strengthens the influence of the focal company within its group, and external integration directly affects innovation [22,23,30,53,56,57].…”
Section: Cooperation Network Diversity Of Companies With Fdimentioning
confidence: 99%
“…Furthermore, it can serve as a guide for other countries like Spain, which are neither advanced nor behind in R&D [73,74]. There is also a wealth of information provided by PITEC as compared with the information offered by EU CIS countries for other countries on Europe's borders [57]. Additionally, among Spanish companies, there is increasing technological interaction with diverse and geographically dispersed actors [59].…”
Section: Database and Samplementioning
confidence: 99%
See 1 more Smart Citation
“…7 Since 2005, the response rate to the survey is above 95%. While the sample is representative of the population of large firms (with 200 or more employees), the representativeness of small and medium-sized firms is biased toward firms having internal and/or external R&D. Regarding the geographic distribution of foreign subsidiaries within Spain, Holl and Rama (2016) have shown that PITEC is highly representative.…”
Section: Methodsmentioning
confidence: 99%
“…They help overcome the liability of foreignness (Zaheer, 1995) by lessening the difficulty of doing business in a foreign market environment (Goerzen et al, 2013) through higher accessibility and less uncertainty (Blevins et al, 2016). Admittedly, agglomeration disadvantages can exist in global cities (Mariotti et al, 2010;Narula & Santangelo Grazia, 2012) as, for example, anticipated knowledge outflows can make global cities unattractive to research-intensive firms (Holl & Rama, 2016); however, the evidence suggests that there is no negative impact from knowledge outflows on firm-level performance (Erden et al, 2014;Eriksson, 2011).…”
Section: Hypothesis Developmentmentioning
confidence: 99%